Research Methodology: methods and techniques - Kothari C R (New Delhi New Age International Publishers, 2010)
This second edition has been thoroughly revised and updated and efforts have been made to enhance the usefulness of the book. In this edition a new chapter The Computer : Its Role in Research have been added keeping in view of the fact that computers by now become a indispensable part of research equipment. The other salient feature of this revised edition, subject contents have been developed and restructured at several places. New problems have also been added in various chapters. Adoption of appropriate methodology is an essential characteristic of quality research studies irrespective of the discipline with which they are related. The present book provides the basic tenets of methodological research so that researchers may become familiar with the art of using research methods and techniques. The book contains introductory explanations of several quantitative methods enjoying wide use in social sciences. It covers a fairly wide range, related to Research Methodology. The presentations are uniformly economical and cogent. Illustrations given are meaningful and relevant. The book can be taken as a well-organised guide for researchers whose methodological background is not extensive. The book is primarily intended to serve as a textbook for social science students of all Indian universities. It will also serve as a text for the students of M.Phil, Management, and students of various institutes. It will serve all practitioners doing research of one form or other in a general way.
An Introduction Defining the Research Problem Research Design Sampling Design Measurement and Scaling Techniques Methods of Data Collection Processing and Analysis of Data Sampling Fundamentals Testing of Hypotheses-I (Parametric or Standard Tests of Hypotheses) Chi-Square Test Analysis of Variance and Covariance Testing of Hypotheses-II (Non parametric or Distribution-Free Test) Multivariate Analysis Techniques Interpretation and Report Writing The Computer: ITS Role in Research Appendix-Selected Statistical Tables.
Includes bibliographical references and index
Keywords: Research Methodology; Research Techniques